High-temperature-resistant silicon-based aerogel and preparation method thereof

By introducing the aluminum oxide layer on the surface of SiO2 aerogel using chemical liquid deposition method, the problem of insufficient high temperature resistance of SiO2 aerogel in the prior art is solved, and the high temperature stability and low thermal conductivity of the material are improved. Suitable for industrial applications.

CN119160901APending Publication Date: 2024-12-20AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411183023.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has problems such as complex preparation process, many process steps, and reduced insulation ability of materials in improving the high temperature resistance of SiO2 aerogels, especially in large-size materials and industrial applications.

Method used

The aluminum oxide layer was introduced on the surface of SiO2 aerogel by chemical liquid deposition. The aluminum oxide layer with nanoscale thickness was formed by reacting with the surface hydroxyl and alkoxy groups, and hydrophobic treatment was carried out to prepare a high-temperature modified SiO2. Aerogel.

Benefits of technology

It has achieved the improvement of high temperature resistance of SiO2 aerogel, maintained the low thermal conductivity of the material and the channel connectivity, simplified the process flow, reduced costs, and was suitable for industrial-scale high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160901A_ABST
    Figure CN119160901A_ABST
Patent Text Reader

Abstract

The invention discloses high-temperature-resistant silicon-based aerogel and a preparation method thereof, and belongs to the field of silicon compounds. The preparation method comprises the following steps: firstly, preparing SiO2 aerogel containing surface hydroxyl groups, then introducing aluminum oxide on the surface of a SiO2 skeleton by adopting a chemical liquid phase deposition method, and then carrying out hydrophobic treatment to obtain the high-temperature-resistant aluminum modified SiO2 aerogel which can be stored for a long time. According to the invention, the low heat-conducting property of the material can be guaranteed, and the temperature resistance of the SiO2 aerogel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of silicon compounds, and in particular relates to a high temperature resistant silicon-based aerogel and a preparation method thereof. Background Art

[0002] SiO2 aerogel is the most mature aerogel system. Its pearl-chain-like particles are small in size, have a slender three-dimensional skeleton, and have a high surface energy. It is generally believed that traditional SiO2 aerogels have good thermal insulation properties in medium and low temperature applications below 600°C, but the internal structure will sinter and collapse in long-term use environments with temperatures exceeding 600°C. The macroscopic manifestation is that the material shrinks significantly, greatly reducing the material's heat-insulating effect, limiting its application in high-temperature environments. The temperature resistance of SiO2 aerogel can be improved through process optimization or doping, compounding and other means.

[0003] Patent CN109621849A discloses a method for preparing silica-coated alumina composite aerogel at normal pressure, wherein a pre-synthesized alumina wet gel is immersed in a mixed solution of a silicon source and ethanol, and then subjected to a hydrophobic treatment in a modified solution of hexamethyldisiloxane and n-hexane, and then dried in an oven at normal pressure to prepare silica-coated alumina aerogel. The silica on the surface of alumina can inhibit the shrinkage of alumina aerogel in a high-temperature environment, thereby improving the performance of the composite material in a high-temperature environment.

[0004] Patent CN115108809A discloses a method of using orthosilicate and inorganic aluminum source as co-precursors, acid-base two-step catalysis to prepare aluminum-modified silica sol, introducing inorganic ceramic fiber preforms by vacuum pressure impregnation, and then supercritical drying with ethanol to obtain a modified silica aerogel thermal insulation composite material with a maximum operating temperature of 1100°C. Similarly, Ceram. Int., 2022 (48): 15006-15016 introduces a method of adding a small amount of aluminum chloride to silicic acid to prepare a silica-aluminum hybrid sol, and after gelation and surface modification, drying at normal pressure to prepare aluminum-modified silica sol. Its mechanism is as follows: Figure 1 These studies show that the introduction of Al elements into SiO2, especially the formation of a local electronegative -Si-O-Al-structure on the particle surface, can inhibit the sintering of silicon oxide nanoparticles at high temperatures and improve high temperature stability.

[0005] Chemical vapor deposition (or infiltration) can form a controllable and uniform metal oxide heterogeneous layer on the surface of the solid material skeleton. For example, a nano-thick layer composed of Al2O3, ZnO2, TiO2, carbon materials, etc. deposited on the surface of SiO2 aerogel can improve the temperature resistance of silica aerogel by inhibiting the movement of nanoparticles and enhancing the radiation effect (CN114804819B, Chem. Mater. 2021(33):5572-5583).

[0006] Zu et al. used chemical liquid deposition (CLD) to react the hydroxyl and alkoxy groups on the surface of Al2O3, ZrO2, and TiO2 wet gels with the hydroxyl groups on the surface of SiO2 sol to form a core-shell structure wet gel coated with SiO2 sol, and obtained a composite aerogel after supercritical drying with ethanol. The advantages of CLD method to introduce heterogeneous SiO2 on the surface are to enhance the structure and thermal stability of the aerogel and inhibit the growth and phase change of crystals.

[0007] CN113716572A discloses a method for preparing an alumina-silicon oxide aerogel composite material, wherein the prepared SiO2 gel is immersed in the prepared Al2O3 sol to obtain a silicon-alumina composite wet gel, and the -Al-O- bonds on the surface of the Al2O3 sol react with Si-OH and Si-OR (R represents an alkyl group) on the surface of the SiO2 wet gel to form an alumina gel on the surface of the SiO2 gel, thereby protecting the SiO2 aerogel network structure at high temperatures.

[0008] CN108467045A discloses a method for preparing a self-hydrophobic aerogel of a dual silicon source system by chemical liquid deposition. The wet gel is placed in an ethanol solution of partially hydrophilized polydimethylsilicone oil by chemical liquid deposition. The purpose is to deposit the partially hydrophilized polydimethylsilicone oil on the surface of the wet gel to strengthen the skeleton structure. However, solvent replacement is still required before subsequent normal pressure drying to achieve normal pressure drying.

[0009] The main disadvantages of improving the temperature resistance of SiO2 aerogel by adding other types of metal oxides in the prior art are as follows:

[0010] (1) Al is introduced into SiO2 gel by co-hydrolysis of single-molecule precursors. Since the hydrolysis rate of organic / inorganic aluminum salts (including aluminum isopropoxide, aluminum sec-butoxide, aluminum nitrate, aluminum chloride, aluminum sulfate, etc.) is extremely fast, it is difficult to match the sol-gel time window of the silicon precursor. It is necessary to use a chelating agent and finely adjust the preparation parameters to prepare silica-alumina gel, and the preparation process is relatively complicated.

[0011] (2) The silica-alumina aerogel is prepared by pre-forming silica sol and aluminum sol co-gel. Since aluminum sol is difficult to stably exist in the pH range of 4-9, it is challenging to control the silica-alumina co-gel time window. If the gel time is too fast, it is difficult to prepare engineering samples. In addition, this method takes a long time to prepare and has complicated process steps.

[0012] (3) The preparation of silica-alumina aerogel by introducing Al2O3 sol into the pre-formed SiO2 gel can avoid the matching problem of the time window of the co-hydrolysis-co-gelation process of silica-alumina precursors. However, due to the particle impregnation process, it is difficult to control the quality of the Al2O3 layer formed on the surface of the SiO2 skeleton, and there is also the disadvantage of clogging the nanopores.

[0013] (4) Chemical vapor deposition (ALD) can form a high-quality metal aluminum oxide deposition layer on the surface of SiO2 aerogel, but the current chemical vapor deposition equipment can only process centimeter-sized samples and is not suitable for large-sized aerogel materials used in the industry. At the same time, the chemical vapor deposition equipment and preparation process are complex, and the requirements for equipment and operators are high.

[0014] The three existing methods of introducing aluminum oxide into SiO2 wet gels - impregnation of aluminum sol, impregnation of aluminum precursors, and co-gel of silicon-aluminum precursors - easily cause blockage of the three-dimensional interconnected channels of the gel, reducing the thermal insulation capacity of the material. The wet gel channels are rich in water, which makes the hydrolysis of the aluminum precursor uncontrollable and self-condenses, making it difficult to achieve uniform grafting of aluminum oxide on the surface of the SiO2 skeleton. The hydrolysis and condensation conditions and time windows of the silicon-aluminum precursor are difficult to match, and auxiliary materials need to be added, and the reaction conditions need to be finely controlled to achieve co-gel, which makes preparation difficult. Summary of the invention

[0015] The purpose of the present invention is to propose a high-temperature resistant silicon-based aerogel and a preparation method thereof. First, SiO2 aerogel containing surface hydroxyl groups is prepared, and then aluminum oxide is introduced on the surface of the SiO2 skeleton by chemical liquid deposition (ALD), and then hydrophobic treatment is performed to obtain a SiO2 aerogel coated with an aluminum oxide layer that can be stored for a long time and is resistant to high temperatures, that is, aluminum-modified SiO2 aerogel.

[0016] The technical solution adopted by the present invention is as follows:

[0017] A method for preparing a high temperature resistant silicon-based aerogel comprises the following steps:

[0018] (1) adding a silicon precursor and an acid catalyst to water for hydrolysis, and then adding an alkali catalyst for gelation to obtain a SiO2 wet gel;

[0019] (2) drying the SiO2 wet gel to obtain a SiO2 aerogel, placing the aerogel in a container, adding an aluminum precursor organic solution that reacts with hydroxyl groups and alkoxy groups on the surface of the SiO2 aerogel, and performing a chemical liquid deposition reaction to deposit an aluminum oxide layer with a nanometer thickness on the surface of the SiO2 aerogel to obtain a high temperature resistant aluminum-modified SiO2 aerogel;

[0020] (3) Drying the aluminum-modified SiO2 aerogel in a ventilated environment and then performing gas-phase hydrophobicity or liquid-phase hydrophobicity can obtain a high-temperature resistant aluminum-modified SiO2 aerogel.

[0021] Furthermore, in step (1), the solid content of SiO2 in the SiO2 wet gel (i.e., the proportion of SiO2 relative to the total mass of water + silicon precursor) is 15% to 30%, and the amount of silicon precursor added is determined according to the solid content.

[0022] Furthermore, in step (1), the silicon precursor is selected from an organic silicon source or an inorganic silicon source, wherein the organic silicon source is one of methyl orthosilicate, ethyl orthosilicate, polyethyl silicate Si-40, methyl (ethyl) trimethoxysilane, methyl (ethyl) triethoxysilane, dimethyl (ethyl) dimethoxysilane, dimethyl (ethyl) diethoxysilane, vinyl trimethoxysilane, and phenyl trimethoxysilane; and the inorganic silicon source is one of sodium silicate, silicic acid, and silica sol.

[0023] Furthermore, in step (1), for the organic silicon source that is immiscible with water, a phase separation inhibitor is also added simultaneously or in advance, such as a cationic surfactant such as ethanol, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, or a non-ionic surfactant such as F123, polyethylene glycol, etc., and the amount of the phase separation inhibitor used is 1% to 5% of the total mass of the silicon precursor and water.

[0024] Furthermore, in step (1), the acid catalyst is selected from one of the small molecular acids such as nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid, citric acid, maleic acid, hydrofluoric acid, etc. After the acid catalyst is added, the pH of the solution is between 2 and 7.5, and the hydrolysis time is 0.5 to 24 hours.

[0025] Furthermore, in step (1), the base catalyst is one of water-soluble small molecule organic quaternary ammonium bases such as ammonia water, NH4F, tetramethyl(ethyl)ammonium hydroxide, tetramethyl(ethyl)ammonium fluoride, etc., and the amount of the base catalyst used is 0.01% to 3% of the total mass of the silicon precursor and water.

[0026] Furthermore, the gelling condition in step (1) is aging at 40-200° C. for 24-96 hours.

[0027] Furthermore, in step (2), the drying method is atmospheric pressure drying, supercritical drying or freeze drying, wherein the silicon precursor containing non-hydrolyzable organic groups is dried at atmospheric pressure, and other silicon precursors are replaced with ethanol after aging and then supercritically dried or freeze dried.

[0028] Furthermore, the SiO2 aerogel dried at normal pressure in step (2) is calcined at 350-500°C for 0.5-2h to remove the surface alkyl groups.

[0029] Furthermore, in step (2), the aluminum precursor is one of aluminum isopropoxide, aluminum sec-butoxide, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate, and sodium aluminate.

[0030] Furthermore, the organic solvent used in the aluminum precursor organic solution in step (2) is one of n-hexane, cyclohexane, n-heptane, pentane, ethanol, and isopropanol, the mass ratio of the aluminum precursor to the volume of the organic solvent is 1 g / (50-400 mL), and the mass ratio of the non-hydrophobic SiO2 aerogel to the aluminum precursor after drying is 1:(0.01-0.2).

[0031] Furthermore, the temperature of the chemical liquid deposition reaction in step (2) is room temperature to 90°C, and the reaction time is 0.5 to 9 hours; when the reaction temperature is higher than the volatilization temperature of the organic solvent, a condensation reflux device is configured to dissolve the aluminum precursor and make the SiO2 aerogel below the liquid surface of the organic solvent.

[0032] Furthermore, in step (2), the thickness of the aluminum oxide layer is 2 to 15 nm.

[0033] A high temperature resistant silicon-based aerogel is an aluminum-modified SiO2 aerogel prepared by the above preparation method.

[0034] Beneficial effects achieved by the present invention:

[0035] 1. When the present invention adopts supercritical drying or freeze drying, the surface of the dried SiO2 aerogel is rich in hydroxyl groups -OH and some alkoxy groups -OR; when atmospheric pressure drying is adopted, the surface alkyl groups of the dried SiO2 aerogel are removed after high-temperature calcination to obtain more surface hydroxyl groups. Then, on the surface of the SiO2 aerogel rich in hydroxyl groups, a small molecule aluminum precursor is hydrolyzed with the surface hydroxyl groups and a small amount of alkoxy groups to uniformly graft an aluminum oxide layer of nanometer thickness, thereby strengthening the skeleton structure, basically not affecting the pore connectivity and porosity, ensuring the low thermal conductivity of the material, and improving the temperature resistance of the SiO2 aerogel.

[0036] 2. Compared with the chemical vapor deposition method, the present invention only requires a simple and controllable chemical liquid deposition treatment between the surface hydrophobicity to improve the temperature resistance of the substrate. It does not require a complicated vacuum system and air intake system, is simple to operate, has relatively mild reaction conditions, is low in cost, and is easy to promote in industry.

[0037] 3. The present invention performs chemical liquid deposition on the obtained dry aerogel to introduce aluminum oxide with higher temperature resistance, which not only achieves the effect of strengthening the skeleton, but also utilizes the electronegative Si-O-Al bonds formed at the interface to inhibit neck sintering through repulsion.

[0038] 4. The present invention uses an organic solvent with low polarity, low surface tension and high volatility. After the chemical liquid deposition reaction is completed, the organic solvent fills the aerogel pores. Due to the low polarity, low surface tension and high volatility of the organic solvent, a high-temperature resistant aluminum-modified SiO2 aerogel that can be stored for a long time can be obtained by simple ventilation and drying and gas-phase hydrophobic or liquid-phase hydrophobic treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the mechanism of improving the temperature resistance of SiO2 aerogel by doping Al in the prior art.

[0040] Figure 2 The present invention is a flow chart of preparing high temperature resistant silicon-based aerogel in an embodiment. DETAILED DESCRIPTION

[0041] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0042] The following three embodiments provide the steps for preparing high temperature resistant silicon-based aerogels. Figure 2 As shown, the prepared Al-modified high temperature resistant SiO2 aerogel, i.e., the high temperature resistant aluminum-modified SiO2 aerogel in the above technical solution, refers to the high temperature resistant silicon-based aerogel to be prepared in the present invention. In the embodiment, after the aerogel is prepared, the shrinkage rate and the specific surface area before and after calcination are measured. A pair of ratios is also given below as a control, which lacks the key steps in the preparation method of the present invention, and the prepared aerogel is also measured for related parameters.

[0043] Embodiment 1:

[0044] Take 100g of deionized water, add tetraethyl orthosilicate according to 20% SiO2 solid content, add 2g of 1mol / L HNO3 solution, stir and hydrolyze for 1h, then add 2g of 1mol / L ammonia water, stir and mix thoroughly. After gelation, age at 120°C for 3 days, replace the aged wet gel with ethanol 3 times within 2 days to obtain alcohol gel, and perform supercritical drying. After drying, place 2g of SiO2 aerogel in a container with a condensation reflux device, add aluminum isopropoxide n-hexane solution, the mass of aluminum isopropoxide is 0.15g, and the mass of n-hexane solution is 50mL. In the heating condensation reflux device, react at 80°C for 1.5 hours, and deposit a nano-thick aluminum oxide layer on the surface of the SiO2 aerogel particles. After the solution cools to room temperature, take out the Al surface-modified SiO2 aerogel, dry it, and use hexamethyldisiloxane for gas phase hydrophobicity to obtain Al-modified high-temperature resistant SiO2 aerogel that can be stored for a long time.

[0045] The Al-modified high temperature resistant SiO2 aerogel was heat treated at 800℃, and its shrinkage was measured to be 2.4%. The specific surface area distribution before and after calcination was 542.5m 2 / g and 493.4m 2 / g, the thermal conductivity before and after the test is 0.022W / m / k and 0.023W / m / k.

[0046] Embodiment 2:

[0047] Take 100g of deionized water, add tetraethyl orthosilicate according to the SiO2 solid content of 27%, then add 2g of 1mol / L HNO3 solution, stir and hydrolyze for 1h to obtain silica sol, then add 3g of 1mol / L ammonia water, mix vigorously, let the gel stand and age at 60℃ for 4 days. The aged gel is replaced with ethanol 3 times within 2 days to obtain alcohol gel, which is supercritically dried. After drying, 2g of SiO2 aerogel is placed in a container with a condensation reflux device, and isopropanol aluminum cyclohexane solution is added, the mass of isopropanol aluminum is 0.3g, and the mass of n-hexane solution is 60mL. In the heating condensation reflux device, react at 90℃ for 1 hour to deposit a nanometer-thick aluminum oxide layer on the surface of the SiO2 aerogel particles. After the solution is cooled to room temperature, the Al-modified SiO2 aerogel is taken out, dried, and gas-phase hydrophobic with hexamethyldisiloxane to obtain Al-modified high-temperature resistant SiO2 aerogel that can be stored for a long time.

[0048] The Al-modified high temperature resistant SiO2 aerogel was heat treated at 1000℃, and its shrinkage was measured to be 3.3%. The specific surface area distribution before and after calcination was 320.2m 2 / g and 290.6m 2 / g, the thermal conductivity before and after the test is 0.026W / m / k and 0.027W / m / k.

[0049] Embodiment 3:

[0050] Take 100g of deionized water, add 4g of hexadecyltrimethylammonium bromide and 0.2g of citric acid, add methyltriethoxysilane according to 23% of SiO2 solid content (the proportion of water + silicon precursor total mass), stir vigorously for hydrolysis for 4h, add 0.3g of 1mol / L NH4F solution, stir for 20min, let gel stand, and age at 180℃ for 1.5 days. The aged gel is directly dried at normal pressure for 4 days, and then gradient dried at 60℃ and 120℃ for 6h. Then, it is calcined at 450℃ for half an hour to remove the surface alkyl. 3g of alkyl-free aerogel is placed in a container with a condensation reflux device, and sec-butanol aluminum n-heptane solution is added, the mass of sec-butanol aluminum is 0.4g, and the mass of n-heptane solution is 120mL. In the heating condensation reflux device, react at 90℃ for 2 hours to deposit a nano-thick aluminum oxide layer on the surface of the SiO2 aerogel particles. After the solution cools to room temperature, the Al-modified SiO2 aerogel is taken out, dried, and subjected to gas-phase hydrophobicization with hexamethyldisiloxane to obtain Al-modified high-temperature resistant SiO2 aerogel that can be stored for a long time.

[0051] The Al-modified high temperature resistant SiO2 aerogel was heat treated at 900℃, and its shrinkage was measured to be 3.6%. The specific surface area distribution before and after calcination was 280.7m 2 / g and 227.8m 2 / g, the thermal conductivity before and after the test is 0.033W / m / k and 0.034W / m / k.

[0052] Embodiment 4:

[0053] Take 100g of deionized water, add 3g of hexadecyltrimethylammonium chloride and 0.3g of acetic acid, add methyltrimethoxysilane according to 15% SiO2 solid content, stir vigorously for hydrolysis for 24h, add 0.5g of 1mol / L NH3·H2O solution, stir for 15min, let gel stand, and age at 150℃ for 4 days. The aged gel is directly dried at normal pressure for 3 days, and then gradient dried at 60℃ and 150℃ for 5h. Then, it is calcined at 350℃ for two hours to remove the surface alkyl. 2g of alkyl-free aerogel is placed in a sealed container, and isopropanol aluminum cyclohexane solution is added. The mass of isopropanol aluminum is 0.2g, and the mass of n-heptane solution is 60mL. The reaction is sealed at 30℃ for 8h, and a nano-thick aluminum oxide layer is deposited on the surface of SiO2 aerogel particles. After the solution cools to room temperature, the Al-modified SiO2 aerogel is taken out, dried, and subjected to gas-phase hydrophobicization with hexamethyldisiloxane to obtain Al-modified high-temperature resistant SiO2 aerogel that can be stored for a long time.

[0054] The Al-modified high temperature resistant SiO2 aerogel was heat treated at 700℃, and its shrinkage was measured to be 0.8%. The specific surface area distribution before and after calcination was 330.2m 2 / g and 315.6m 2 / g, the thermal conductivity before and after the test is 0.031W / m / k and 0.031W / m / k.

[0055] Comparative Example 1:

[0056] Take 100g of deionized water, add ethyl orthosilicate according to 20% SiO2 solid content (the proportion of water + silicon precursor total mass), add 2g of 1mol / L HNO3 solution, stir and hydrolyze for 1h, then add 1.5g of 1mol / L ammonia water, stir and mix thoroughly. After gelation, age at 120℃ for 3 days, replace the aged wet gel with ethanol 3 times within 2 days to obtain alcohol gel, and perform supercritical drying. Use hexamethyldisiloxane for gas phase hydrophobicity to obtain SiO2 aerogel that can be stored for a long time.

[0057] The SiO2 aerogel was heat treated at 800℃ and its shrinkage was measured to be 22%. The specific surface area distribution before and after calcination was 632.5m 2 / g and 63.4m 2 / g, the thermal conductivity before and after the test is 0.021W / m / k and 0.058W / m / k.

[0058] Comparative Example 2:

[0059] Take 100g of deionized water, add 3g of hexadecyltrimethylammonium chloride and 0.3g of acetic acid, add methyltrimethoxysilane according to 15% SiO2 solid content, stir vigorously for hydrolysis for 24h, add 0.5g of 1mol / L NH3·H2O solution, stir for 15min, let gel stand, and age at 150℃ for 4 days. The aged gel is directly dried at normal pressure for 3 days, then gradient dried at 60℃ and 150℃ for 5h, and gas-phase hydrophobicized with hexamethyldisiloxane to obtain high-temperature resistant SiO2 aerogel that can be stored for a long time.

[0060] The SiO2 aerogel was heat treated at 700℃ and its shrinkage was measured to be 19%. The specific surface area distribution before and after calcination was 330.2m 2 / g and 315.6m 2 / g, the thermal conductivity before and after the test is 0.031W / m / k and 0.057W / m / k.

[0061] The test data of the above embodiments and comparative examples are shown in Table 1 below.

[0062] Table 1 Summary of test data of embodiments and comparative examples

[0063]

[0064] By comparing the test data in Table 1 above, it can be seen that the introduction of aluminum oxide on the surface of the aerogel by chemical liquid deposition significantly improves the temperature resistance of the material. After high-temperature treatment, the shrinkage rate is greatly controlled (within 5%), and the specific surface area is well retained, indicating that the pore structure is supported and protected, and the aerogel structure is maintained at high temperature, which helps to effectively inhibit high-temperature gas phase heat transfer and play a high-temperature heat-insulating role.

[0065] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a high temperature resistant silicon-based aerogel, characterized in that: The following steps are involved: (1) adding a silicon precursor and an acid catalyst to water for hydrolysis, and then adding an alkali catalyst for gelation to obtain a SiO2 wet gel; (2) drying the SiO2 wet gel to obtain a SiO2 aerogel, placing the aerogel in a container, adding an aluminum precursor organic solution that reacts with hydroxyl groups and alkoxy groups on the surface of the SiO2 aerogel, and performing a chemical liquid deposition reaction to deposit an aluminum oxide layer with a nanometer thickness on the surface of the SiO2 aerogel to obtain a high temperature resistant aluminum-modified SiO2 aerogel; (3) Drying the aluminum-modified SiO2 aerogel in a ventilated environment and then performing gas-phase hydrophobicity or liquid-phase hydrophobicity can obtain a high-temperature resistant aluminum-modified SiO2 aerogel.

2. The preparation method according to claim 1, characterized in that The solid content of SiO2 in the SiO2 wet gel in step (1) is 15% to 30%, and the amount of silicon precursor added is determined according to the solid content.

3. The preparation method according to claim 1, characterized in that: In step (1), the silicon precursor is selected from an organic silicon source or an inorganic silicon source, wherein the organic silicon source is one of methyl orthosilicate, ethyl orthosilicate, polyethyl silicate Si-40, methyl (ethyl) trimethoxysilane, methyl (ethyl) triethoxysilane, dimethyl (ethyl) dimethoxysilane, dimethyl (ethyl) diethoxysilane, vinyl trimethoxysilane, and phenyl trimethoxysilane; the inorganic silicon source is one of sodium silicate, silicic acid, and silica sol; for the organic silicon source that is immiscible with water, a phase separation inhibitor is also added simultaneously or in advance, and the phase separation inhibitor is a cationic surfactant or a non-ionic surfactant, and the amount of the phase separation inhibitor used is 1% to 5% of the total mass of the silicon precursor and water.

4. The preparation method according to claim 1, characterized in that: In step (1), the acid catalyst is selected from one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid, citric acid, maleic acid, and hydrofluoric acid. After the acid catalyst is added, the pH of the solution is between 2 and 7.5, and the hydrolysis time is 0.5 to 24 hours. The base catalyst is one of ammonia water, NH4F, tetramethyl(ethyl)ammonium hydroxide, and tetramethyl(ethyl)ammonium fluoride. The amount of the base catalyst is 0.01% to 3% of the total mass of the silicon precursor and water.

5. The preparation method according to claim 1, characterized in that: The gelling condition in step (1) is aging at 40-200° C. for 24-96 hours.

6. The preparation method according to claim 1, characterized in that: The drying method in step (2) is atmospheric pressure drying, supercritical drying or freeze drying, wherein the silicon precursor containing non-hydrolyzable organic groups is dried at atmospheric pressure, and other silicon precursors are replaced by ethanol after aging, and then supercritically dried or freeze dried; the SiO2 aerogel after atmospheric pressure drying is calcined at 350-500°C for 0.5-2h to remove the surface alkyl groups.

7. The preparation method according to claim 1, characterized in that: In step (2), the aluminum precursor is one of aluminum isopropoxide, aluminum sec-butoxide, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate, and sodium aluminate; the organic solvent used in the aluminum precursor organic solution is one of n-hexane, cyclohexane, n-heptane, pentane, ethanol, and isopropanol, the mass ratio of the aluminum precursor to the volume of the organic solvent is 1g / (50-400mL), and the mass ratio of the non-hydrophobic SiO2 aerogel to the aluminum precursor after drying is 1:(0.01-0.2).

8. The preparation method according to claim 1, characterized in that: The temperature of the chemical liquid deposition reaction in step (2) is room temperature to 90°C, and the reaction time is 0.5 to 9 hours. When the reaction temperature is higher than the volatilization temperature of the organic solvent, a condensation reflux device is configured to dissolve the aluminum precursor and make the SiO2 aerogel below the liquid surface of the organic solvent.

9. The preparation method according to claim 1, characterized in that: The thickness of the aluminum oxide layer in step (2) is 2 to 15 nm.

10. A high temperature resistant silicon-based aerogel, characterized in that: The aluminum-modified SiO2 aerogel is prepared by the preparation method according to any one of claims 1 to 9.